若(1-2x)^9=a0+a1x+a2x^2+.+a9x^9,则a1+a9=?
1个回答
a1=C(1,9)(-2)=-18,
a9=C(9,9)(-2)^9=-512,
所以a1+a9=-18-512=-530.
相关问题
若(x-2)^9 = a0 + a1 (x-1) + a2 (x-1)^2 + ...+ a9 (x-1)^9 ,则 a
若(x-2)^9=a0+a1(x-1)+a2(x-1)^2+...+a9(x-1)^9,则a8=?
设(1-3x)^9=a0+a1X+a2x^2+a3x^3...+a9x^9,则|a0|+|a1|+|a2|+.+|a9|
已知(x-2)^9=a0x^9+a1x^8+...+a9,则a1+a2+...+a9=
1.若多项式x^2+x^10=a0+a1(x+1)+...+a9(x+1)^9+a10(x+1)^10,则a9=
若x^10+x^4+1=a0+a1(x+1)+a2(x+1)^2+……+a9(x+1)^9+a10(x+1)^10,则a
X+X^2+……+X^9+X^10=A0+A1(1+X)+A2(1+X)^2……+A9(1+X)^9+A10(1+X)^
已知(1-2x)^9=a0+a1x+a2x²+···a8x^8+a9x^9,那么a1+a2+···a8+a9=
如果x+x^2+x^3+…+x^9+x^10=a0+a1(1+x)+a2(1+x)^2+…+a9(1+x)^9+a10(
设(x+2)^9=a0+a1x+a2x^2+...+a9x^9 求(a1+3a3+5a5+7a7+9a9)^2--(2a